On the smoothness of the generalized solution of a parabolic system in domains with conic points on the boundary - Nguyen Manh Hung; Pham Trieu Duong (Український математичний журнал, 2004)
We consider the first initial boundary-value problems for parabolic systems in domains with conic points on a boundary. We study the smoothness of their solutions with respect to space variables.